Studying second language acquisition from a qualitative perspective - Wojtaszek, Adam; Gabrys-Barker, Danuta (Second Language Learning and Teaching, 2014)
This book presents a selection of empirical papers dealing with second and multiple language acquisition, in which qualitative research methodology is employed. Each of the studies reported in individual chapters is based on a solid theoretical background and an overview of studies in a given area. Although the main focus is on qualitative methods, some of the papers demonstrate the complementarity of quantitative and qualitative approaches in studying language acquisition.